La educación formal en cuestionamiento: voces y vivencias de las y los estudiantes de un liceo del cantón central de Heredia - Gómez Torres, Juan (2010)
This article presents the results of a participant action research applied in a High School in Heredia, in which the life experiences and voices of the involved students are taking into account. Moreover, their critics towards formal education and its curricular organization lead to a proposal on alternative school experiences that can be called a paralleled curriculum. This type of curriculum breaks up with the Costa Rican public high school official curriculum by inserting the students’ ways of being and doing.